Probabilistic based evaluation of the structural reliability achieved for a typical building designed according to SANS 517:2009 and SANS 10162- 2:2010 - Oosthuizen, Frederik du Toit (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng)--Stellenbosch University, 2011.